Response of Banded Whistler Mode Waves to the Enhancement of Solar Wind Dynamic Pressure in the Inner Earth's Magnetosphere. Issue 17 (10th September 2018) - Yu, Xiongdong; Yuan, Zhigang; Li, Haimeng; Huang, Shiyong; Wang, Dedong; Yao, Fei; Funsten, H. O.; Wygant, J. R.
Abstract: With observations of Van Allen Probe A, in this letter we display a typical event where banded whistler waves shifted up their frequencies with frequency bands broadening as a response to the enhancement of solar wind dynamic pressure. Meanwhile, the anisotropy of electrons with energies about several tens of keV was observed to increase. Through the comparison of the calculated wave growth rates and observed wave spectral intensity, we suggest that those banded whistler waves observed with frequencies shifted up and frequency bands broadening could be locally excited by these hot electrons with increased anisotropy. The current study provides a great in situ evidence for the influence on frequencies of banded whistler waves by the enhancement of solar wind dynamic pressures, which reveals the important role of solar wind dynamic pressures playing in the frequency properties of banded whistler waves. Plain Language Summary: In the inner magnetosphere, broadband whistler waves are often taken into account in understanding the evolution of the Earth's radiation belts. Solar wind dynamic pressures, as a driving factor, can influence whistler‐mode waves not only on their occurrence, but also on their frequencies. However, the proof for the influence of the solar wind pressure on the frequency properties of the excited banded whistler waves in the inner magnetosphere has not been uncovered.With observations of Van Allen Probe A, we display a typical event that broadband whistler waves can be locally excited as a response to the enhancement of solar wind dynamic pressure. As the solar wind pressure enhanced, the normalized frequencies of broadband whistler waves became higher. Through the comparison of the calculated wave growth rates and observed wave spectral intensity, we suggest that broadband whistler waves could be locally excited with higher frequencies by these hot electrons with increased anisotropy. The current study provides a great in situ evidence for the influence on frequencies of banded whistler waves by the enhancement of solar wind dynamic pressures, which reveals the important role of solar wind dynamic pressures playing in the frequency properties of banded whistler waves. Key Points: This paper provides in situ evidence of local excitation of broadband whistler mode waves outside plasmapause in the inner magnetosphere The normalized frequencies of broadband whistler waves become higher with enhancements of the solar wind pressure This paper has revealed the frequency properties of broadband whistler mode waves by solar wind dynamic pressure enhancements